Review of cold spraying and its use for metallic glass coatings. Issue 16 (2nd November 2019) - Su, Juan; Kang, Jia-jie; Yue, Wen; Ma, Guo-zheng; Fu, Zhi-qiang; Zhu, Li-na; She, Ding-shun; Wang, Hai-dou; Wang, Cheng-biao
ABSTRACT: Cold spraying (CS), a solid-state spraying technology, is expected to become an appropriate supplementary for traditional spraying methods owing to its plenty of merits such as high deposition efficiency, low temperature and little influence on the particles/substrate. The most reported researches are bulk alloys fabricated by CS. However, the systematic introduction and cold-sprayed metallic glass coatings have not been summarised. Therefore, in this paper, the international research status of CS including equipment structure, spraying process and parameters, advantages and disadvantages, deposit features and bonding mechanism were introduced. By using this technology, the successful researches about Fe-, Al-, Ni-, Cu- and Zr- based amorphous alloy coatings are reported. To overcome the limitations, further development and solutions were proposed.